Perencanaan Dan Pengelolaan Keuangan Untuk UMKM Pada Masyarakat Pasir Jaka Desa Cimanggu, Cisalak Subang Jawa Barat - Priyanto, Aria Aji; Nurismalatri, Nurismalatri; Rudy, Rudy (LPPM Universitas Pamulang, 2024)
The aim of this community service is for the community to understand financial planning and management for MSMEs in the Pasir Jaka community, Cimanggu village. In community service, it was found that in carrying out financial management of MSMEs, several things must be paid attention to, including: Evaluating current financial conditions; Control and supervise cash flow; Separating personal finances from business finances; Providing reserve funds; Planning protection and business; Create targets and spending plans; Make plans and strategies to achieve targets; and manage debt wisely. This is conveyed through presentation methods and outreach to the community. The results of community service are expected to make MSMEs even better in their management, for example in lending and borrowing, business owners or MSME actors must also pay attention to important things including: Take debt if necessary; Take debt only for productive purposes (business expansion, building a shop, buying a vehicle for sales, etc.); The maximum total installment debt is 30% of income; Do not borrow from illegal financial services institutions; and Calculate your ability to pay before applying for a loan.